Rough Ideal Statistical Convergence via Generalized Difference Operators in Intuitionistic Fuzzy Normed Spaces - Chawla, Meenakshi; Kaur, Manpreet; Antal, Reena (Communications in Mathematics and Applications, 2024)
This study focuses on investigating the concept of rough ideal statistical convergence for generalized difference sequences in intuitionistic fuzzy normed spaces. We have studied the algebraic and topological properties of rough ideal statistical limit points for generalized difference sequence. Apart from this, we also investigated rough ideal statistical cluster points, the relation between rough I-statistical limit points and rough I-statistical cluster points for generalized difference sequence in intuitionistic fuzzy normed spaces.